2015
DOI: 10.1016/j.rse.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four EVI-based models for estimating gross primary production of maize and soybean croplands and tallgrass prairie under severe drought

Abstract: Berrien III, "Comparison of four EVI-based models for estimating gross primary production of maize and soybean croplands and tallgrass prairie under severe drought" (2015). Accurate estimation of gross primary production (GPP) is critical for understanding ecosystem response to climate variability and change. Satellite-based diagnostic models, which use satellite images and/or climate data as input, are widely used to estimate GPP. Many models used the Normalized Difference Vegetation Index (NDVI) to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 68 publications
6
57
0
Order By: Relevance
“…NDVI and EVI are perhaps the most widely used VIs for monitoring vegetation conditions and estimating GPP (Dong et al., ; Sims et al., ; Sjöström et al., ; Xiao & Moody, ; Xiao et al., ). The newly proposed near‐infrared reflectance of vegetation (NIR v ), the product of total scene NIR reflectance and NDVI, has been shown to be better related to GPP than NDVI or NIR alone (Badgley, Field, & Berry, ).…”
Section: Methodsmentioning
confidence: 99%
“…NDVI and EVI are perhaps the most widely used VIs for monitoring vegetation conditions and estimating GPP (Dong et al., ; Sims et al., ; Sjöström et al., ; Xiao & Moody, ; Xiao et al., ). The newly proposed near‐infrared reflectance of vegetation (NIR v ), the product of total scene NIR reflectance and NDVI, has been shown to be better related to GPP than NDVI or NIR alone (Badgley, Field, & Berry, ).…”
Section: Methodsmentioning
confidence: 99%
“…It is frequently obtained from remote sensing data using vegetation indices (VIs) [16][17][18][19][20]. Some authors use the VIs as proxies of both ε and f APAR and rewrite Equation (1) as GPP = VI × VI × PAR [21,22]. In the latter case, both broad-band VIs and narrow-band indices can be considered.…”
Section: A Theoretically Sound Approachmentioning
confidence: 99%
“…Dong et al . [] suggested that remote sensing data‐driven models that do not include water limitation factors performed much worse during drought periods. However, even for the models discussed above which consider water stress, their performances are not satisfied [ Liu et al , ; Schaefer et al , ].…”
Section: Introductionmentioning
confidence: 99%